2001
DOI: 10.1093/jnen/60.9.885
|View full text |Cite
|
Sign up to set email alerts
|

Detection of HIV-1 Gene Sequences in Hippocampal Neurons Isolated from postmortem AIDS Brains by Laser Capture Microdissection

Abstract: We employed laser capture microdissection to remove individual pyramidal neurons from the CA1, CA3, and CA4 regions of formalin-fixed, paraffin-embedded hippocampus from 8 AIDS brains and 2 HIV-1-seronegative normal brains. We amplified HIV-1 gag and nef gene sequences using separate, double round PCR reactions for each of the primer sets. In all 3 hippocampal regions, amplification efficiency was best with sequence length between 284 and 324 bp; HIV-1 nef gene sequences were more common than HIV-1 gag sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 48 publications
3
76
0
Order By: Relevance
“…Both animal and tissue culture studies have shown that gp120 produces cell death in rodent hippocampal neurons (Brenneman et al, 1988;Lipton et al, 1995). A human study assessing the CA1, CA3, and CA4 regions of the hippocampus from eight AIDS-infected brains further supports the finding that specific regions of the hippocampus are particularly vulnerable to the virus or its components (Torres-Munoz et al, 2001). The selective vulnerability of hippocampal regions for HIV-1 infection is demonstrated by the expression of HIV-1 chemokine co-receptors on hippocampal pyramidal neurons.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Both animal and tissue culture studies have shown that gp120 produces cell death in rodent hippocampal neurons (Brenneman et al, 1988;Lipton et al, 1995). A human study assessing the CA1, CA3, and CA4 regions of the hippocampus from eight AIDS-infected brains further supports the finding that specific regions of the hippocampus are particularly vulnerable to the virus or its components (Torres-Munoz et al, 2001). The selective vulnerability of hippocampal regions for HIV-1 infection is demonstrated by the expression of HIV-1 chemokine co-receptors on hippocampal pyramidal neurons.…”
Section: Discussionmentioning
confidence: 74%
“…Results revealed evidence of direct HIV-1 infection of neurons as one potential mechanism for neuronal injury or neuronal death. In contrast to studies demonstrating the presence of HIV-1 in neurons (Bagasra et al, 1996;Torres-Munoz et al, 2001;Trillo-Pazos et al, 2003) other studies report the lack of neurons infected by HIV-1 (Takahashi et al, 1996;Thompson et al, 2004). A study which reported HIV-1 infection of macrophages and microglia in addition to a more latent infection of astrocytes, could not detect HIV-1 infected neurons and/or oligodendrocytes (Takahashi et al, 1996).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…31 Laser capture microdissection has been used successfully in the study of several human brain diseases, including the HIV-1-infected brain, subacute sclerosing panencephalitis, Parkinson's disease, and Huntington's disease. [32][33][34][35][36][37][38][39] In the current study, only cases with HAD and HIVE (as well as HIV-1-positive controls) were used. Thus, work in NeuroAIDS has progressed to the point where cell-specific studies will be able to elucidate additional information using novel approaches.…”
Section: Introductionmentioning
confidence: 99%
“…More recent investigations have focused on applying LCM to the study of the central nervous system. These have included genome-wide gene expression analyses using DNA microarrays, as well as expression analyses of individual genes using reverse-transcriptase polymerase chain reaction (RT-PCR) (Jin et al, 1999;Kamme et al, 2003;Lu et al, 2004;Mutsuga et al, 2004;Torres-Munoz et al, 2001;Ye et al, 2003).…”
Section: Introductionmentioning
confidence: 99%